Analiza porównawcza zachowań osobowościowych w relacjach "matka-syn" i "ojciec-syn" = Comparative analysis of personality behavior in the "mother-son" and "father-son" relations - Senko, Tatiana (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article, the author presents views on a father's and a mother's role in a family and describes a "mother-son", a "father-son" relation. There were given the characteristics of the contemporary image of the parent with a son in the context of family contacts. The main research problems were: analyze the correlation between personality parents, personality and behavior of children.
Keywords: matka; ojciec; syn; relacje rodziców z synami; formy zachowań osobowościowych; mother; father; son; relations between mother and son; father and son; forms of personal behaviours